Effect of polymer morphology on P3HT-based solid-state dye sensitized solar cells: an ultrafast spectroscopic investigation. - Kumar, R; Grancini, G; Petrozza, A; Abrusci, A; Snaith, H; Lanzani, G (Optical Society of American (OSA), 2013)
Solid-state dye sensitized solar cell devices are fabricated with poly(3-hexylthiophene) (P3HT) as the hole transporting layer. Upon annealing treatment we obtained ≈ 70% increase in the device efficiency compared to un-annealed devices. Our investigation, by means of ultrafast transient absorption spectroscopic characterization, correlates the increased device performances to a more efficient hole-transfer at the dye/polymer interface in the thermally treated P3HT.